Arahan Pengelolaan Persampahan di Kota Pare-Pare: (Studi Kasus: Kecamatan Bacukiki Barat) - Andi Heydi Maharani Bachmid; Kamran Aksa; Rimba Arief; Arista Asrib (Journal of Urban Planning Studies, 2023)
This study aims to determine the influencing factors and operational directions in waste management in Bacukiki Barat District, Pare-Pare City. This research is qualitative as material for consideration and reference material in analyzing descriptively. Research variables include storage, collection, transportation, final disposal, and operational techniques. The correlation analysis method is to determine whether there is a linear relationship between variables, then a qualitative descriptive analysis is carried out to provide direction for operational waste management. Based on the results of the correlation analysis where the factors causing non-optimal waste management are collection, transportation and final disposal so that the directives for the solid waste operational system are for containers to group garbage and election facilities so that they are differentiated using colored labels and closed containers as well as providing TPS and TPST in residential areas and carrying out provision of waste banks for 3R management.